Effectiveness of Independent Science Project Plan (ISPP) In Enhancing Scientific Inquiry Skills of Grade 7 Filipino Students - Deliguin, Larjay Hipolito (Future Science / FSH-PH Publications, 2024)
The Independent Science Project Plan (ISPP) was used to improve the science inquiry skills of 100 Science 7 students from 4 secondary public schools in Castillejos District, Division of Zambales, Philippines. A quasi-experimental research design was used, and it required a 50-item pre-test and post-test that were validated, and pilot tested by the researcher. Mean analysis, correlated and independent samples tests, and rate of improvement (ROI) are the statistical tools utilized for analysis. Findings revealed there is a significant difference in the level of scientific inquiry skills of the participants before and after the implementation of the strategy. There is a significant difference in the MPS scores between the control and experimental group during the post-test involving all the scientific inquiry skills. When compared to the control group, the experimental group had a much better degree of proficiency in asking questions about the world, in designing and conducting the investigation, in employing different strategies to obtain information, and in communicating results, compared to the control group. Also, the teachers agreed in their being well-quipped with knowledge and skills in delivering distance learning classes through integrating technology into the curriculum, teacher’s preparation, and on the available facilities in conducting distance learning for science teaching. The end outcome is a clear indication that the method worked as intended.